Xenoenxerto ósseo trabecular bovino desmineralizado associado ao plasma rico em plaquetas, em falhas ósseas no rádio de coelhos - Faria, Laura Melgaço (2016)
In the clinics of small animals is common the appearance of patients with fractures with significant bone loss or pathological cases as delayed union and non-union bone. There are many scientific papers about preparation techniques grafts, but still a need to evaluate new techniques that are more easily used, easy to obtain and which enable a faster and more effective bone consolidation. Thus it has been justified conducting an experimental animal model that tested the association of xenograft with platelet-rich plasma (PRP), as well a possibility of forming another option of a bone bank for grafting. The fragments were collected from the distal femur epiphysis of bovines, then they were fragmented, demineralized and processed chemically. A bone failure of one cm was created in the middle third in rabbit radio, which were divided into three groups. The first was the control group (GI), the second one was treated with chemically processed demineralized xenograft (GII), and the third was filled with the same graft and added with platelet-rich plasma (GIII). The graft site was evaluated radiographically and histologically at 30 and 60 postoperative days. The ostectomy area filled with the xenograft was replaced with large amount of bone tissue, in an organized and precocious way when compared to the control group, with no rejection. However the association of xenograft with PRP did not result in a satisfactory consolidation process.